Sponsorship of national and regional professional paediatrics associations by companies that make breast-milk substitutes: evidence from a review of official websites. Issue 8 (10th August 2019) - Grummer-Strawn, Laurence M; Holliday, Faire; Jungo, Katharina Tabea; Rollins, Nigel
Abstract : Objectives: Professional paediatrics associations play an important role in promoting the highest standard of care for women and children. Education and guidelines must be made in the best interests of patients. Given the importance of breastfeeding for the health, development and survival of infants, children and mothers, paediatric associations have a particular responsibility to avoid conflicts of interest with companies that manufacture breast-milk substitutes (BMSs). The objective of this study was to investigate the extent to which national and regional paediatric associations are sponsored by BMS companies. Methods: Data were collected on national paediatric associations based on online searches of websites and Facebook pages. Sites were examined for evidence of financial sponsorship by the BMS industry, including funding of journals, newsletters or other publications, conferences and events, scholarships, fellowship, grants and awards. Payment for services, such as exhibitor space at conferences or events and paid advertisements in publications, was also noted. Results: Overall, 68 (60%) of the 114 paediatric associations with a website or Facebook account documented receiving financial support from BMS companies. Sponsorship, particularly of conferences or other events, was the most common type of financial support. The prevalence of conference sponsorship is highest in Europe and the Americas, where about half of the associations have BMS company-sponsored conferences. Thirty-one associations (27%) indicated that they received funding from BMS companies as payment for advertisements or exhibitor space. Only 18 associations (16%) have conflict of interest policies, guidelines, or criteria posted online. Conclusion: Despite the well-documented importance of breastfeeding and the widespread recognition that commercial influences can shape the behaviours of healthcare professionals, national and regional paediatric associations commonly accept funding from companies that manufacture and distribute BMS. Paediatric associations should function without the influence of commercial interests.